Evaluation of Scientific Article Writing Training Program Using CIPP Model: Case Study in Directorate of Research and Community Service - Arianda, Yoga Dwi; Madani, Faisal; Badrujaman, Aip; Priyanto, Sugeng (LPPM Undiksha, 2025)
The main issue underlying this study is the still low quality and quantity of scientific publications by lecturers in Indonesia, particularly in reputable national and international journals. This situation is exacerbated by the limited availability of truly structured scientific writing training programs that are based on participants' needs and include a continuous evaluation mechanism. Many training programs focus solely on technical aspects without considering differences in participants’ academic backgrounds, the effectiveness of teaching methods, or the long term impact on academic productivity. This study aims to evaluate a scientific article writing training program organized by the Directorate of Research and Community Service, using the CIPP evaluation model (Context, Input, Process, Product). The study employs a mixed methods approach, with data collection techniques including questionnaires, semi structured interviews, and documentation. The evaluation results show that the training addressed participants' contextual needs (context), had fairly adequate input, especially in terms of facilitators and materials, but still faced challenges in the training process (process), particularly regarding participant interaction and teaching methods. Overall, the product of the training (product) indicated an improvement in participants’ writing skills, with most able to produce draft scientific articles. The study recommends improvements in training methodology and feedback mechanisms to enhance the effectiveness and long term impact of the training.